2013
DOI: 10.1111/1751-2980.12013
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic papillary large‐balloon dilation following limited sphincterotomy for the removal of refractory bile duct stones: Experience of 169 cases in a single Chinese center

Abstract: EPLBD following limited EST is an effective and safe approach for the removal of large biliary duct stones, especially for those refractory cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…In the systematic review by Kim et al, 32 the incidence of pancreatitis following EPLBD (balloon diameter: 12-20 mm) with EST was 2.4% (0%-13.2%), which included mild-to-moderate pancreatitis in 98.4% and severe pancreatitis in one patient who eventually died. Furthermore, in six RCTs 15,41,82,89,91,96 and five meta-analyses, 53,94,95,121,122 it was reported that there was no significant difference in the incidence of pancreatitis between EPLBD with EST and EST alone.…”
Section: Statement 4-4mentioning
confidence: 99%
“…In the systematic review by Kim et al, 32 the incidence of pancreatitis following EPLBD (balloon diameter: 12-20 mm) with EST was 2.4% (0%-13.2%), which included mild-to-moderate pancreatitis in 98.4% and severe pancreatitis in one patient who eventually died. Furthermore, in six RCTs 15,41,82,89,91,96 and five meta-analyses, 53,94,95,121,122 it was reported that there was no significant difference in the incidence of pancreatitis between EPLBD with EST and EST alone.…”
Section: Statement 4-4mentioning
confidence: 99%
“…Subsequently, EPLBD has been used in various clinical trials for the treatment of CBD stones in patients without intestinal reconstruction. These clinical observations have indicated that the success rate of stone extraction in a single attempt ranged from 83% to 100%, with a need for mechanical lithotripsy in 0-39% of the cases [2,[12][13][14][15][16]. Furthermore, the complication rate of the procedure is not very high (range 4-16%).…”
Section: Discussionmentioning
confidence: 99%
“…reported in a multicenter study that transpapillary large balloon dilation with endoscopic sphincterotomy may have a low risk of post‐ERCP pancreatitis because this method can preserve the function of the sphincter. These studies also reported that when large balloon dilation was performed with sphincterotomy or precut fistulotomy, but not when performed alone without previous sphincterotomy, there were no differences in complications compared with conventional methods . Some studies also showed that transpapillary large balloon dilation for removal of CBD stones without previous sphincterotomy was safe and effective in patients with large bile duct stones; however, these studies included a small number of patients …”
Section: Discussionmentioning
confidence: 99%
“…These studies also reported that when large balloon dilation was performed with sphincterotomy or precut fistulotomy, but not when performed alone without previous sphincterotomy, there were no differences in complications compared with con-ventional methods. 12,13,[19][20][21][22] Some studies also showed that transpapillary large balloon dilation for removal of CBD stones without previous sphincterotomy was safe and effective in patients with large bile duct stones; however, these studies included a small number of patients. 11,14 In cases of precut fistulotomy, which have a small incisional direction, such as sphincterotomy, the risk of pancreatitis may not be increased.…”
Section: Discussionmentioning
confidence: 99%